Pengaruh pemasaran jejaring media sosial Instagram Digital Amoeba dan keterkaitan konsumen terhadap niat beli konsumen - Istifaroh, Haifaninda; Rachmawati, Indira (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Social media network marketing in a company attracts consumers to relate to each other so that it will provide an increase in consumer purchase intentions. The purpose of this study was to determine the effect of social media network marketing on Instagram Digital Amoeba and the relationship between consumers and consumers' purchase intentions. This study uses a quantitative research methodology with a causal associative research approach with data analysis techniques using Structural Equation Model (SEM) and analysis tools using AMOS 24.0. The population in this study were all Instagram Digital Amoeba followers. The sample size in this study was 314 respondents with the characteristics of already following Instagram @digitalamoeba; aged 18-54 years; work as students, employees, and entrepreneurs; and Indonesian Citizens. The results of the study indicate that social media network marketing has a significant effect on consumer purchase intentions with consumer linkage acting as an intervening variable in influencing social media users to have consumer purchase intentions.